ARCH: Cluster Head Optimization Using Autonomous Cluster Heads Re-Election Algorithm in Wireless Sensor Networks - Govindaraj D. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Wireless Sensor Networks (WSNs) are vital in many applications. To improve network efficiency and extend system longevity, these nodes must be organized into clusters, with a Cluster Head (CH) governing each cluster. Network performance and energy efficiency depend on Cluster Heads, thus it’s important to choose and optimize them correctly. In order to optimize the selection of Cluster Heads in WSNs, this study presents a novel technique known as the Autonomous Cluster Head Re-Election (ARCH) algorithm. To address challenges like energy depletion and node failures, the ARCH algorithm prioritizes the dynamic re-election of Cluster Heads in response to changing network circumstances. Nodes are able to evaluate their immediate surroundings, communication habits, and energy levels to autonomously choose the best candidate for the CH job via the algorithm’s use of autonomous decision-making processes. By tackling the issues with conventional static CH assignment techniques, the self-organizing and dynamic methodology employed guarantees efficient and robust WSN operation.